1987
DOI: 10.1002/ajim.4700120512
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos disease in sheet metal workers: II. Radiologic signs of asbestosis among active workers

Abstract: A review of chest x-rays of 707 currently employed New York metropolitan area sheet metal workers found that 29.3% of the workers with 20 years or more of union membership (a surrogate for years of exposure) had radiologic abnormalities characteristic of parenchymal and/or pleural asbestosis, with 18.6% having abnormalities characteristic of parenchymal asbestosis (International Labor Organization [ILO] classification 1/0 or higher) and 17.4% of pleural asbestosis. The prevalence of abnormalities characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…This prevalence was higher than that observed in the general population (2.9% in USA) [Rogan et al, 1987] and similar to other reported screenings of low-intensity asbestosexposure populations, such as elevator construction workers [Bresnitz et al, 1993], pipe®tters and plumbers [Sprince et al, 1985], sheet-metal workers [Michaels et al, 1987], and electricians [Hodgson et al, 1988].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This prevalence was higher than that observed in the general population (2.9% in USA) [Rogan et al, 1987] and similar to other reported screenings of low-intensity asbestosexposure populations, such as elevator construction workers [Bresnitz et al, 1993], pipe®tters and plumbers [Sprince et al, 1985], sheet-metal workers [Michaels et al, 1987], and electricians [Hodgson et al, 1988].…”
Section: Discussionsupporting
confidence: 88%
“…This exposure pro®le may favor the development of pleural rather than parenchymal abnormalities [Copes et al, 1985]. In our cohort, the ratio of prevalence rates of pleural to parenchymal disease (6.2 on standard chest radiograph and 3.2 on HRCT scans) is as high as observed for other intermittent exposures [Baker et al, 1985;Bourbeau et al, 1988;Lilis et al, 1986;Michaels et al, 1987;Rosenstock et al, 1988;Schwartz et al, 1990]. Greater prevalence ratios of pleural to parenchymal abnormalities are also found in subjects with non-occupational exposure, which is presumably lower and more intermittent than occupational exposure [Health Effects Institute, 1991].…”
Section: Discussionmentioning
confidence: 50%
“…These findings support the results of our previous mortality study [Zoloth and Michaels, 19851, as well as those of two investigations into the prevalence of asbestos disease among sheet metal workers. [Michaels et al, 1987;Baker et al, 19851.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of pneumoconiosis in the construction industry has been studied in such specific occupational groups as insulators, plumbers, pipefitters, sheet metal workers, and female construction workers [Baker et al, 1985;Fischbein et al, 1979;Kivekas, 1989;Michaels et al, 1987;Soda and Yamazaki, 1981;Sprince et al, 19851 and among workers with known asbestos exposure [Hedenstierna et al, 19811. Existing prevalence data are thus limited to workers with established mineral dust exposure. However, many other occupational groups in construction work may be exposed to asbestos and quartz dusts.…”
Section: Introductionmentioning
confidence: 99%